School Health Services Practices in Primary Schools as Reported by Teachers in Wassit and The-Qar Governorate in Iraq - Sameeha Naser Abed; Rawaa Kamel Abed; Fatimah Haran Daham (Journal of Techniques, 2022)
School health plays an important role in preventive and curative management that will reflect positively on young children, all workers in school, and academic performance. The objective of this study was to assess the school health services practices in primary schools in Wassit and Thi-Qar governorates. A descriptive cross-sectional study design using a self-administered questionnaire to obtain information on the practice of school health services as reported by the schoolteachers. This study was conducted between October 2018 and March 2019. Data were analyzed using SPSS. The result of the study revealed that the statistical significance has been proved for two governorates related to practices therapeutic services (P <0.05) and the practice level was found poor among (71.62%) in Wassit governorate, while the score was observed as good and acceptable (52.7%) in Thi-Qar governorate. Statistical significance has been proved for two governorates related to practices preventive services (p<0.05) and the practice level was found poor among (71.62%) in the Wassit governorate and (59%) in the Thi-Qar governorate. In addition, the result of this study showed that the level of the overall practice of school health services in primary schools was poor (89.46%). The results of this study indicated that there is a weakness in the practice of preventive services in primary schools in two governorates. As observed from the study, the practice of therapeutic services in the Thi-Qar governorate is quite satisfactory and higher than in the Wassit governorate. Therefore, the study concludes that the overall practice of school health services is poor.